Determinan Pemilihan Tempat Persalinan Oleh Ibu Bersalin - Lisda Handayani; Elvine Ivana Kabuhung; Yunita Afriani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background : One reason why maternal mortality rate still high is deivery not at health care facilities. Informationof north tapin health center said there had been 470 delivery and while non health facilities about 43,2 %. For whichfigures obtained conclude that delivery in Tapin did not reach target years 2016 who was targeted delivery serviceat health facilities appropriate standard 100 %Objective : analysis determinant factors of delivery election at North Tapin central public healthMethods : Quantitative researched by approach cross sectional, taken by total sampling about 62 delivered in january 2017 .The stastik used chi square and simple logistic regressionResult : there are 43,5 % mother who has deivery at health care facilities, while non health care facilities are 56.5%. Correlation factors of cultural (p value = 0,000), ANC (p value = 0,001), knowledge (p value = 0,000), deliveryfees (p value = 0,001), income (p value = 0,154), access to health care facilities (p value = 0,315), and support family (p value = 0,411). Dominant determine factors of delivery selection is delivery fee (p=0,008, OR=11,712).Conclusion : bivariate analysis result shown there are relation between cultural factors , a pregnancy , knowledge, and the delivery fee with selection of delivery at haealth care facilities. The most dominant determine is deliveryfeesKeywords : delivery , culture , ANC, knowledge , income , delivery fee , access healt care , support family